Melatonin Mitigates Cd-Induced Growth Repression and RNA m6A Hypermethylation by Triggering MMR-Mediated DNA Damage Response - Zihan Tang; Hetong Wang; Xianpeng Wang; Richard A. Ludlow; Zhouli Liu; Min Zhang; Qijiang Cao; Wan Liu; Qiang Zhao (Plants)
Melatonin (MT) has been found to mitigate cadmium (Cd) toxicity with negligible environmental risks. It remains poorly understood as to how MT mitigates Cd-induced growth repression and regulates RNA m6A methylation. We aimed to elucidate the effect of MT on growth repression and RNA m6A methylation in Arabidopsis (Arabidopsis thaliana) exposed to Cd stress. MT mitigated, on average, 13.96% and 8.42% of growth repression resulting from Cd and mismatch repair (MMR) deficiency. The ameliorative effect on Cd stress was reduced by 70.56% and 34.23% in msh2 and msh6 mutants, respectively. With distinct dose–effect relationships, m6A hypermethylation responded to Cd stress rather than Cu stress, which was further elevated in MMR-deficient seedlings. MT reduced m6A levels by 22.98% even without stress induction, whereas the depressed m6A levels in MMR-deficient seedlings, greatly exceeding those in the WT. The “writer” and “eraser” gene expression responsible for m6A methylation was reduced with the concentration of stresses due to MT, but VIR and ALKBH9B no longer responded to Cd stress in msh2 and msh6. Despite the remarkable repression, MMR gene expression was regularly promoted by MT under Cd and Cu stress. Our study provides novel insights into the molecular mechanisms underlying the restorative effects of MT on growth repression and m6A methylation regulation, which shed light on Cd phytoremediation.